TREN MEMILIH JURUSAN UNTUK MELANJUTKAN STUDI DI PERGURUAN TINGGI (Studi Pada Siswa-Siswi SLTA Sederajat Kelas XII Di Kota Bengkulu) - Vethy Octaviani; Linda Astuti (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2026)
This study aims to examine the trends in choosing a major for continuing studies at university among 12th-grade high school students in Bengkulu City. This study uses a qualitative approach with descriptive methods. Data collection techniques in this study were conducted through interviews, observation, and documentation. The data analysis technique used an interactive analysis model consisting of three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the choice of major for continuing studies among high school students in Bengkulu City is the result of a complex communication process. Internal factors such as personal interests, talents, and motivation are the main basis for major selection. Most students choose majors that align with their interests, abilities, and future aspirations that have been formed since school. External factors, especially the role of parents and teachers, function as supporters who strengthen students' decisions. The support and guidance provided are helpful and not coercive, thus making students more confident in their chosen major. Social media also plays a role as a source of cognitive information in understanding majors and the world of college. However, social media is not the main determinant, but rather serves as an additional reference in the decision-making process. Thus, the trend in student major selection is the result of the interaction between internal, external, and social media factors. Keywords: Major Selection, College, Trends